Novel modified criteria for sperm morphology in oocyte insemination could reduce ICSI rates without affecting IVF outcomes - Tseng-Kai Lin; Leng-Lai Chan; Tsung-Hsuan Lai; Hsiao-Ching Lo (Taiwanese Journal of Obstetrics & Gynecology, 2023)
Objective: To evaluate the IVF outcomes of conventional insemination for less severe teratozoospermia (LST) patients (sperm morphology >2% and <4% normal forms and total motile sperm count ≥10 × 106) and normal sperm patients defined by WHO criteria 2010 in the interest of reducing intracytoplasmic sperm injection (ICSI) rate in IVF. Materials and methods: In this retrospective study, a total of 330 patients were recruited in the conventional IVF insemination. Among them, there were 76 patients in LST group and 254 patients in the normal sperm group. Fertilization rate, abnormal fertilization rate, embryo quality, implantation rate, chemical pregnancy rate, clinical pregnancy rate, abortion rate and live birth rate were assessed. Results: No statistical differences were achieved in the percentage of normally fertilized eggs (85.9% vs. 85.8%), abnormal fertilization rates of 1 PN (2.76% vs. 3.01%) or 3 PN (5.70% vs. 6.30%), good embryo rate (52.4% vs. 51.5%), implantation rate (20.9% vs 17.5%), chemical pregnancy rate (45.1% vs. 39.4%), clinical pregnancy rate (36.0% vs. 31.7%), live birth rate (28.9% vs. 26.7%) and abortion rate (9.6% vs. 10.2%) between LST group and normal sperm group regardless of the sperm morphology. Conclusion: Patients with less severe teratozoospermia may not need ICSI in their IVF treatment since the outcomes particularly the fertilization rates were not affected by the less compromised sperm morphology at all when compared with the normal sperm patients.